2003
DOI: 10.1111/j.1572-0241.2003.07387.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of accuracy of the noninvasive Helicobacter pylori stool antigen test in patients with gastroduodenal ulcer bleeding

Abstract: The HpSA test gave a high number of false- positive results in patients with PUB, probably because of blood constituents cross-reacting in the enzyme immunoassay. The HpSA test is not accurate for testing H. pylori infection in patients with PUB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…While some authors report a prevalence of over 90% (19), other authors have described a lower prevalence, between 20 and 70% (17,30). These discrepancies may be due to the different diagnostic methods used, since the techniques employed to diagnose this infection in this type of patients have often been reported to be less sensitive (17,18,32).…”
Section: Discussionmentioning
confidence: 97%
“…While some authors report a prevalence of over 90% (19), other authors have described a lower prevalence, between 20 and 70% (17,30). These discrepancies may be due to the different diagnostic methods used, since the techniques employed to diagnose this infection in this type of patients have often been reported to be less sensitive (17,18,32).…”
Section: Discussionmentioning
confidence: 97%
“…The first On the other hand, it has been postulated that H. pylori stool antigen tests in patients with gastroduodenal ulcer bleeding are inaccurate, with low sensitivity in some evaluations, 32 and low specificity in other cases. 33,34 Recently, Gisbert et al 35 described…”
Section: Discussionmentioning
confidence: 99%
“…It is an accurate test in all age groups of children too [19] . However, Peitz et al reported that the diagnostic accuracy, in particular the sensitivity, of the HpSA stool test was reduced by upper gastrointestinal bleeding, and a negative test result should be confirmed by a further diagnostic method [20,21] . Although the HpSA test seems to be less accurate than the UBT, both UBT and stool antigen tests are reliable noninvasive tests for monitoring the efficacy of H pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%